The Role of Wanagama as a Healing Forest during the COVID-19 Pandemic - Dwiko Budi Permadi; Ratih Madya Septiana; Handojo H Nurjanto; Rini Pujiarti; Ananto Triyoga (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
The increase in COVID-19 cases had resulted in the Government of Indonesia establishing a National Health Emergency on the 1st of April 2020, followed by Large-scale Social Restrictions (PSBB). This condition had directly impacted people’s lives in the countryside, namely the reduced ability to meet the needs of life, especially the need for food. In addition, quarantine rooms had been required to accommodate reactive rapid test patients because their number had exceeded the capacity of the hospitals that treated COVID-19 patients. Furthermore, facilitation and instrumentation to improve people’s ability from stagnating economic activities in the countryside are also necessary. This situation led to an emergency response at Wanagama Healing Forest and the anticipated activities after the pandemic. The community service activity was implemented for six months in the Wanagama Healing Forest, involving the target groups of village communities surrounding the forest, task force of COVID-19, and reactive rapid test patients throughout Gunung Kidul Regency. The community service activities consisted of (1) improving food security and purchasing power of the communities, (2) improving knowledge and awareness of COVID-19, (3) provision of quarantine houses for reactive patients of Gunung Kidul Regency, and (4) revitalization of Mangium House as a partnership house to produce honey bee, essential oil and community empowerment.